East Africa Strategic Futures Workshop for Non-State Actors - SID (2012)
CCAFS and the Regional office of the Society for International Development for Eastern Africa (SID-EA), an international network of individuals and organizations dedicated to international cooperation and development, collaborated to invite experts and members of leading institutions in civil society and the private sector to take part in the East Africa Strategic Non-State Actors Workshop in Nairobi. The workshop specifically set out to train regional actors in the development and use of CCAFS scenarios, as an important decision making tool. It also sought to create a vision for the region’s future in terms of food security, environments and livelihoods in collaboration with non-state actors’.